OPTIMIZATION OF THE GROWTH MEDIA OF Bacillus cereus BACTERIA WITH THE ADDITION OF SKIM MILK AND DIFFERENT CARBON SOURCES - Taufan, Muhammad; Feliatra, Feliatra; Effendi, Irwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
The goal of this research was to find the optimal media for growing B. cereus bacteria with various carbon sources. This study used an experimental method with two Bacillus cereus bacterium isolates, namely B. cereus strain SN7 (isolate N) and a consortium of bacteria isolates (a combination of several B. cereus isolates with different strains). The two isolates were grown in sago liquid waste media, tofu liquid waste media, and molasses liquid waste media supplemented with a protein source, skim milk, with three replications in each treatment. Bacterial culture growth was measured every 6 hours for 24 hours using two methods: the TPC method and bacterial cell biomass measurement. According to the results of this study's measurements, molasses waste media was the best modified medium for B.cereus growth. The difference in growth between the B. cereus strain SN7 bacterial isolates and the consortium cultured on molasses media was not significant. The isolates with the largest number of cell growth were B. cereus consortium isolates, with 2,023 x108 CFU/mL in the TPC method and 1,011 g/mL in the biomass measurement method at 24 hours.